2023
DOI: 10.3390/antibiotics12071220
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole-Triazole Hybrids as Antimicrobial and Antiviral Agents: A Systematic Review

Abstract: Bacterial infections have attracted the attention of researchers in recent decades, especially due to the special problems they have faced, such as their increasing diversity and resistance to antibiotic treatment. The emergence and development of the SARS-CoV-2 infection stimulated even more research to find new structures with antimicrobial and antiviral properties. Among the heterocyclic compounds with remarkable therapeutic properties, benzimidazoles, and triazoles stand out, possessing antimicrobial, anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 175 publications
0
9
0
Order By: Relevance
“…Different studies also confirmed the high potency of triazole and its analogs as anticancer 10 12 , anti-microbial 13 , 14 , anti-inflammatory 15 , 16 , and anti-melanogenic agents as tyrosinase inhibitors. In this category, triazole-benzoimidazole (Compound F) with IC 50 = 9.42 μM is a good example 17 .…”
Section: Introductionmentioning
confidence: 77%
“…Different studies also confirmed the high potency of triazole and its analogs as anticancer 10 12 , anti-microbial 13 , 14 , anti-inflammatory 15 , 16 , and anti-melanogenic agents as tyrosinase inhibitors. In this category, triazole-benzoimidazole (Compound F) with IC 50 = 9.42 μM is a good example 17 .…”
Section: Introductionmentioning
confidence: 77%
“…Benzimidazole is widely used in antihypertensive, antituberculous, anti-inflammatory, antibacterial, antiviral, analgesic, antihypertensive, antibacterial, and rare applications in cardiovascular diseases. , Vitamin B12 consists of benzimidazole, and also thiabendazole, azomycin, chlotrimazole, mebendazole, Omeprazole and albendazole, rabeprazole are the important drugs composed of benzimidazole derivatives. , The synthesis of benzimidazole and quinazoline is 100% atom efficient due to 100% utilization of CO 2 and other substrates . Traditionally, benzimidazole was synthesized from DMF (dimethylformamide) derivatives, formic acid, esters, and methanol. Benzimidazole was synthesized using a basic medium or strong medium, toxic reagents and high temperatures, but nowadays the synthesis is more environmentally friendly and sustainable by using catalysts. , Another important intermediate used in the pharmaceutical industry is quinazolines-2,4­(1 H ,3 H )-diones synthesized by harmful chemicals such as anthranilamide with phosgene, anthranilic acid with urea, and antranilic acid with chlorosulfonyl isocyanate or potassium cyanate (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Benzimidazole possesses a diverse range of biological activities, such as anti-hypertensive [ 11 , 12 ], anti-Alzheimer’s [ 13 ], anti-microbial, anti-viral [ 14 ], anti-diabetic [ 15 , 16 ] and anti-cancer activities [ 17 ]. There are some drug molecules, such as benoxaprofen, albendazole, enviradine, bendamastine, omeprazole and astemizole, which contain a benzimidazole moiety in their skeleton ( Figure 2 ) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%